Safety of Soy Formula in Children With Cow's Milk Protein Allergy - Wasito, Erika; Azzahra, Adelia (Ridwan Institute, 2023)
Cow's milk protein allergy is a common health problem among children. Children with cow's milk protein allergy cannot consume cow's milk or other dairy products because their bodies react to cow's milk proteins. In an effort to meet the nutritional needs of these children, soy formula is a commonly used option. The purpose of this study was to evaluate the safety of soy milk formula in children with cow's milk protein allergy. This study used qualitative research methods. The data collection technique was done by literature study. The data that has been collected was then analyzed using three stages namely data reduction, data presentation and conclusion drawing. The results showed that soy milk formula is generally safe to be given to children with cow's milk protein allergy. Soy milk formula does not cause significant allergic symptoms in children with cow's milk protein allergy. In addition, soy milk formula also fulfills the nutritional needs of children with cow's milk protein allergy. Soy formula contains all the essential nutrients that children need to grow and develop. Based on the results of the study, soy milk formula can be a safe and effective formula option for children with cow's milk protein allergy.